Innovative computational modal analysis of a marine propeller - Uslu, Seckin; Bayraktar, Meral; Demir, Cihan; Bayraktar, Seyfettin (ELSEVIER SCI LTD, 2021)
It is a fact that specifying numerically the natural frequencies of a marine propeller rotating in a water environment is quite difficult due to the problem that arises from the inability to consider the effect of rotation and pressure distribution in the modal acoustic module of the software. In the present study, an alternative approach to the experimental studies is proposed to come through this problem that enables researchers to predict numerically the change in natural frequency of a three-bladed marine propeller. The method based on the fluidstructure interaction (FSI) technique uses the modal stiffness and the modal mass that is calculated from the numerical analysis of a rotating marine propeller in air and then considers the effects of the added mass by utilizing the frequency reduction ratio (FRR) and finally defines the natural frequencies of the rotating propeller in the water. The simulations revealed that the natural frequencies of the propeller decrease substantially in water due to the added mass and the reduction in the natural frequencies with respect to frequencies in the air is 28% for the first, 34% for the second, and the third. Since natural frequencies of a rotating propeller in water cannot be simulated the equivalent stiffness and masses were defined for each frequency from the analyses of propeller rotating in the air. It was concluded that the natural frequency of the propeller decreases when the propeller is placed in water for the same boundary conditions.
Keywords: Marine propeller; Modal analyses; Frequency reduction ratio; Added mass; HYDRO-ELASTIC ANALYSIS; HYDROELASTIC ANALYSIS; ADDED-MASS; VIBRATION ANALYSIS; FEM; INFLOW; Engineering; Oceanography